2018
DOI: 10.1117/1.jbo.23.1.016002
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative photoacoustic imaging of two-photon absorption

Abstract: Photoacoustic tomography (PAT) is a hybrid imaging modality where we intend to reconstruct optical properties of heterogeneous media from measured ultrasound signals generated by the photoacoustic effect. In recent years, there have been considerable interests in using PAT to image two-photon absorption, in addition to the usual single-photon absorption, inside diffusive media. We present a mathematical model for quantitative image reconstruction in two-photon photoacoustic tomography (TP-PAT). We propose a co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 91 publications
(144 reference statements)
0
20
0
Order By: Relevance
“…With the assumptions we have, the result in [5, Theorem 2.1] ensures the well-posedness of the linear transport equation (10) in the L ∞ dξ (Γ − ) → L ∞ (X) framework. This allows Theorem 2.6 of [6] to be reproduced in the Λ We now differentiate (9) twice with respect to ε, and obtain that v • ∇u (2)…”
Section: Based On Propositionmentioning
confidence: 93%
See 1 more Smart Citation
“…With the assumptions we have, the result in [5, Theorem 2.1] ensures the well-posedness of the linear transport equation (10) in the L ∞ dξ (Γ − ) → L ∞ (X) framework. This allows Theorem 2.6 of [6] to be reproduced in the Λ We now differentiate (9) twice with respect to ε, and obtain that v • ∇u (2)…”
Section: Based On Propositionmentioning
confidence: 93%
“…Note that in Proposition A.2, for suitable chosen g ∈ L ∞ dξ (Γ − ), there exists a unique positive solution u (1) to (10) such that u (1) ≥ ε > 0 for some constant ε > 0 depending on g, Ω, σ a , σ s . We…”
Section: Based On Propositionmentioning
confidence: 99%
“…On the other hand, PACT gives a larger penetration depth beyond one centimeter, but at the expense of inferior spatial resolution. To overcome the limitation of PAM, non-linear mechanisms have been introduced such as two-photon absorption [6,21,35]. The phenomenon when an electron transfers to an excited state after simultaneously absorbing two photons can be defined as two-photon absorption.…”
Section: Introductionmentioning
confidence: 99%
“…The mathematical formulation of 2P-PAT was first introduced in [6,21], where the authors consider an optically absorbing and scattering medium Ω ⊂ R n (n ≥ 2). Denoting the density of photons at a point x ∈ Ω as u(x), it was shown that u(x) solves the following semi-linear diffusion equation −∇ • (D(x)∇u(x)) + σ(x)u(x) + µ(x)|u(x)|u(x) = 0, in Ω, u(x) = g(x), on ∂Ω,…”
Section: Introductionmentioning
confidence: 99%
“…Generally, PAM is often used for highresolution imaging within a depth of several millimeters, while PACT is mostly utilized for volumetric imaging with a larger penetration depth beyond one centimeter at the expense of inferior spatial resolution. One of the most recent advances in PAM is super-resolution imaging, enabled by non-linear mechanisms, such as two-photon absorption (8)(9)(10), absorption saturation (11)(12)(13)(14)(15), thermal relaxation (12,16,17), photothermal bleaching (18,19) and reversible photoswitching (6,20,21). Meanwhile, PACT has made significant progress in attaining three-dimensional (3D) (22)(23)(24), real-time (25,26), and whole-body small-animal imaging (27,28) performance.…”
Section: Introductionmentioning
confidence: 99%